Making PGA hazard curve in big cities of bengkulu by using USGS PSHA modified - Chintya Meidina Azwar; Arifan Jaya Syahbana; Anggun Mayang Sari; Muhammad Asrurifak; Hendriyawan Hendriyawan; Masyhur Irsyam (Indonesian Geotechnical Journal, 2022)
The tectonic plate movement that limits the Indonesian territory causes frequent earthquakes because the plates have dynamic rocks properties with varying strengths. The collision of the plates causes fault zones, such as in Bengkulu, a region traversed by the Sumatran fault with a record of many earthquakes. The rapid growth and development of technology could support increased infrastructure development by considering earthquakes a major global hazard. Therefore, this study aimed to create a PGA hazard curve useful in improving infrastructure development in Bengkulu's big cities. Data were sourced from the Book of Indonesian Earthquake Hazard and Source 2017. The United States Geological States Probabilistic Seismic Hazard Analysis (USGS PSHA) software was modified regarding the Ground Motion Prediction Equation (GMPE) database. The GMPE used in this study are (1) BC Hydro (2012) updated for subduction source; (2) Campbel Bozorgnia (2014), Boore Atkinson (2014) and Chiou Young (2014) for shallow crustal source, and (3) Zhao et al. (2006) and Abrahamson et al. (2018) for intraslab, with 500, 1,000, 2,500, 5,000, and 10,000 years return periods. The results obtained using the new GMPE showed a change in the maximum acceleration. The Hazard Curve (HC) and PGA map showed that the Kepahiang and Lebong Districts have the highest PGA values of 1.8070 and 1.8433 g, respectively, for the 10,000 year return period. The lowest value was 0.297g recorded in Rejang Lebong for 500 year return period.